How Classroom Emotional Climate Shapes Motivation in University EFL Contexts: A Mediation Model of Teacher–Student Relationship and Perceived Teacher Autonomy Support - Shakil, Rashed Mahmud; Liana, Jannat-E-Ridowana; Efty, Emtiaz Ahmed; Rafi, Naimur Rahman; Tasnim, Nazifa (Indonesian Journal of Advanced Research, 2026)
The present study examines the mediating influence of teacher–student relationship (TSR) and perceived teacher autonomy support (PTAS) in the association between classroom emotional climate (CEC) and learners’ motivation (LM) among the Bangladeshi university English as a Foreign Language (EFL) learners. Applying a quantitative method, survey data were gathered from 250 EFL-centric learners and analysed through PLS-SEM and SPSS. The results highlight that CEC significantly influences TSR and PTAS, both of which, in turn, positively impact LM. Moreover, TSR and PTAS have partial mediation in the link between CEC and LM. The study extends motivational theory in the context of EFL by underscoring relational, emotional, and autonomy-assisted classroom procedures and provides practical implications for promoting a motivating learning atmosphere in higher education.